ENHANCING BREAST MILK PRODUCTION THROUGH THE EFFECTIVENESS OF MUSIC THERAPY: A STUDY IN TERMS OF FREQUENCY, TYPE, AND DURATION OF MUSIC - Harlinda Widia Putri; Sartika Dwi Yolanda Putri; Siti Ainawati Mumtazah; Puja Maya Sari; Pasuria Sihotang; Esti Widyasari; Sulistyaningsih Sulistyaningsih (Placentum, 2024)
Background: Music therapy is one of the non-pharmacological treatment methods used to increase milk production. Music stimulates the release of the hormone oxytocin and endorphins, so that it can increase milk production. Considering the frequency, type and duration of music is indeed pivotal in music theraphy instead of the music intervention.